Investigations at the Site of the Necropolis of the Ancient Town of Nymphaion - Eremeeva, Anna (Hyperboreus, 2019)
A survey of the excavations of the necropolis of Nymphaion (Kerch) conducted by the expedition of the State Hermitage Museum in 2018.